John Clifford, Militant Evangelicals, and the Colonial Model for ‘Secular’ Schools (1870s-1920s) - Geraldine VAUGHAN (E-REA)
At the time of the enactment of compulsory primary education, the Baptist minister John Clifford, along with other Evangelical pressure groups, advocated for the enforcement of State-funded secular schooling. They defended a ‘secular’ education, i.e. a curriculum infused with a broad Protestant ethos, which should be bestowed upon all children throughout Britain and its empire. For Clifford and militant Evangelicals, British Dominions offered models of State secular schooling because of the effective separation of State and Church within their realms. This article explores the militant Evangelical views on ‘secular’ education, along with the fights waged against (Roman Catholic) denominational schooling. It explores the arguments that enthusiastic Evangelical imperialists brought forward to defend their vision of the ideal Briton – a Protestant citizen free from clerical influence. It also studies the Roman Catholics’ reactions to Evangelical attacks against their separate school system, and investigates the Manitoba School Issue as a test case confronting two opposing worldviews on education, the State, and the Churches.